2019
DOI: 10.3390/ijms20194814
|View full text |Cite
|
Sign up to set email alerts
|

Plant DNA Polymerases

Abstract: Maintenance of genome integrity is a key process in all organisms. DNA polymerases (Pols) are central players in this process as they are in charge of the faithful reproduction of the genetic information, as well as of DNA repair. Interestingly, all eukaryotes possess a large repertoire of polymerases. Three protein complexes, DNA Pol α, δ, and ε, are in charge of nuclear DNA replication. These enzymes have the fidelity and processivity required to replicate long DNA sequences, but DNA lesions can block their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 143 publications
(286 reference statements)
0
22
0
Order By: Relevance
“…Thus, loss of interaction between PRC2 and EARLY IN SHORT DAYS (ESD7), the catalytic subunit of DNA polymerase epsilon (Pol-ε), results in the misexpression of major flowering time regulators such as AGAMOUS (AG), SUPPRESSOR OF OVEREXPRESSION OF CO 1 (SOC1), and FLOWERING LOCUS T (FT) (del Olmo et al, 2010(del Olmo et al, , 2016, whose expression is controlled by PRC2. Loss of other DNA polymerases including Pol-α INCURVATA2 (ICU2) and Pol-δ POLD2 also impacts on H3K27me3 distribution, though a direct link with PRC2 subunits remains to be demonstrated (Pedroza-Garcia et al, 2019). These results provide evidence that interactions of PRC2 with multiple DNA polymerases acting at the replication fork likely play a significant role in the maintenance of H3K27me3 landscapes in plants.…”
Section: Prc2 Binds Several Components Of the Replication Machinerymentioning
confidence: 85%
“…Thus, loss of interaction between PRC2 and EARLY IN SHORT DAYS (ESD7), the catalytic subunit of DNA polymerase epsilon (Pol-ε), results in the misexpression of major flowering time regulators such as AGAMOUS (AG), SUPPRESSOR OF OVEREXPRESSION OF CO 1 (SOC1), and FLOWERING LOCUS T (FT) (del Olmo et al, 2010(del Olmo et al, , 2016, whose expression is controlled by PRC2. Loss of other DNA polymerases including Pol-α INCURVATA2 (ICU2) and Pol-δ POLD2 also impacts on H3K27me3 distribution, though a direct link with PRC2 subunits remains to be demonstrated (Pedroza-Garcia et al, 2019). These results provide evidence that interactions of PRC2 with multiple DNA polymerases acting at the replication fork likely play a significant role in the maintenance of H3K27me3 landscapes in plants.…”
Section: Prc2 Binds Several Components Of the Replication Machinerymentioning
confidence: 85%
“…Duplication of nuclear DNA in eukaryotes is dependent on a multi-protein replication complex including pol α with the associated primase activity and two replicases, pol δ and pol ε. A replication complex bound to DNA forms a replication fork whose movement is sensitive to mutations in the template DNA generated by UV light [220]. Unrepaired DNA lesions including pyrimidine dimers may effectively block the synthesis of a new DNA strand throughout stalling of the replication fork [221].…”
Section: Dna Damage Tolerancementioning
confidence: 99%
“…DDT may occur by two distinct mechanisms [223,224]. Whereas the first is based on TLS [220], the other is dependent on template switching [225]. DDT studies on a yeast model have indicated that the choice between TLS and the template switching mechanism is controlled by ubiquitination of PCNA in response to encountered DNA damage during DNA replication [223].…”
Section: Dna Damage Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…In most organisms, the main DNA polymerase in charge of BER-SP is DNA polymerase [ 72 ]. However, this polymerase is absent in plants [ 73 ]. On the other hand, BER-LP requires a specialized DNAP with strand-displacement activity, that incorporates several nucleotides (10–12 bases) after the processed AP site.…”
Section: Plant Organellar Dna Polymerases Are Involved In Base Excmentioning
confidence: 99%